Hazır giyimde dikiş tekniklerinin görsel etkileri - Bahar, Cihan (My University, 2016)
HAZIR GİYİMDE DİKİŞ TEKNİKLERİNİN GÖRSEL ETKİLERİ Bu çalışma, hazır giyim sektöründe çalışan tasarımcıların yada tasarımcı adaylarının, dikim aşamalarında karşılaştıkları dikiş teknikleri ile ilgili problemleri öncelikle tespit etmeyi hedeflemiştir. Bu tekniklerin doğru yönetilip uygulanması ile de dikişlere ve tasarımlara doğrudan olan görsel etkilerin uygulamalarla gösterilmesi amacını taşır. Üç bölüm şeklinde hazırlanan bu çalışmanın ilk bölümde, hazır giyim sektörünün oluşumunda ve gelişmesinde katkısı bulunan, dikiş tekniklerini oluşturan tüm unsurların tarihçeleri hakkında kısa bilgiler verilmektedir. İkinci bölümde, hazır giyimde kullanılan ve dikiş tekniklerini etkileyen tüm faktörler(dikiş tipleri, dikim tipleri, dikiş iplikleri, malzemeler, teknik ekipmanlar vb.) özellikle de en çok kullanılan dikiş tipleri ve dikim tipleri 3 boyutlu teknik çizimler ile giyim tasarımcılarının bilgilenerek faydalanabileceği şekilde anlatılmıştır. Üçüncü bölümde, tasarım süreçleri kısaca incelenerek, tasarımcıların hangi aşamalarda dikiş tekniklerini belirleyip karar vermeleri gerektiği hakkında bilgi verilip, altı farklı malzeme kullanılarak 41 farklı dikiş tekniği uygulaması yapılmış. Yapılan bu dikiş tekniği uygulamaları tablolar haline getirilip, oluşturdukları görsel etkiler hakkında da değerlendirmeler yapılarak sunulmuştur. Bu çalışmanın sonuç kısmında ise, dikiş teknikleri hakkında yapılan tüm araştırmalar ve uygulamalar sonucunda, dikişin ve dolayısı ile de giysi tasarımının görselliğini doğrudan etkileyen birçok parametre tespit edildi. Tüm parametreler tablo haline getirilip değerlendirilerek paylaşıldı.

VISUAL EFFECTS OF SEWING TECHNIQUE AT APPAREL This study firstly aimed to determine problems related to sewing techniques which designers or designer candidates work at apparel sector faced in sewing phases. It has aim to show visual effects those are directly to sewings and designs with applications via applying these techniques by managing in a true way. Short information concerning history of all factors those contributes to create and improve apparel sector, generates sewing techniques were given in first chapter of this study which was prepared as three chapters. All factors those effect sewing techniques and used in apparel(stitch types, seam types, sewing threads, materials, technical equipment etc.) especially most current stitch types and seam types were explained with three dimensional technical drawings and for clothes designers to get informed and utilize in second chapter. 41 different sewing technique was applied by using 6 different materials by informing about that in which phases designers should specify sewing techniques and decide by examining design phases shortly. These performed sewing technique applications were shaped as tables and were presented by assessing about visual effects they made in third chapter. This study firstly aimed to determine problems related to sewing techniques which designers or designer candidates work at apparel sector faced in sewing phases. It has aim to show visual effects those are directly to sewings and designs with applications via applying these techniques by managing in a true way. Short information concerning history of all factors those contributes to create and improve apparel sector, generates sewing techniques were given in first chapter of this study which was prepared as three chapters. All factors those effect sewing techniques and used in apparel(stitch types, seam types, sewing threads, materials, technical equipment etc.) especially most current stitch types and seam types were explained with three dimensional technical drawings and for clothes designers to get informed and utilize in second chapter. 41 different sewing technique was applied by using 6 different materials by informing about that in which phases designers should specify sewing techniques and decide by examining design phases shortly. These performed sewing technique applications were shaped as tables and were presented by assessing about visual effects they made in third chapter. In conclusion chapter of this study, as a result of all researches and applications made concerning sewing techniques, many parameters those effect sewing’s and therefore clothes design’s visuality were determined. All parameters were shaped as tables and shared by assessment.
Keywords: Dikiş; Teknik